Investigating work‐related stress among health professionals at different hierarchical levels: A cross‐sectional study - Karin A. Peter; Jos M. G. A. Schols; Ruud J. G. Halfens; Sabine Hahn (Wiley, 2020)
Abstract Aim To determine the extent of stress at work among health professionals working in upper‐, middle‐ and lower‐management positions and those not working in management positions. Design Cross‐sectional design and randomly selected hospitals, nursing homes and home care organizations. Methods The study sample included nursing staff and midwives, physicians, medical-technical and medical-therapeutic professionals at all hierarchical levels (N = 8,112). Data were collected using self‐report questionnaires and analysed using multiple regression models. Results Health professionals in upper‐ and middle‐management positions reported higher quantitative demands, severe work-private life conflicts (p < .05) as well as less role clarity in middle‐management positions (B = −1.58, p < .05). In lower‐management positions, health professionals reported higher physical (B = 3.80, p < .001) and emotional demands (B = 1.79, p < .01), stress symptoms (B = 1.81, p < .05) and job dissatisfaction (B = −1.17, p < .05). Health professionals without management responsibilities reported the poorest working conditions in relation to various stressors, job satisfaction (B = −5.20, p < .001) and health‐related outcomes (e.g. burnout symptoms: B = 1.89, p < .01).